The Philippine power sector issues and solutions - Cham, Ma. Rowena M. (The Philippine Review of Economics, 2007)
The Philippine government acknowledges that reliable and affordable power is important to achieve economic development and reduce poverty. In fact, it has been at the forefront for a long time, providing generation and transmission services through the National Power Corporation (NPC). However, NPC failed to deliver and live up to its mandate of providing reliable and affordable electricity. The power crisis in the 1990s, the higher the cost of electricity, and NPC's financial difficulties led to the restructuring of the sector to save this ailing industry. This paper traces the evolution of the power sector, explores the events that brought it to insolvency, and discusses the issues that need to be addressed to restore operational and financial viability.